MAPPING ACTORS IN THE CIRCULAR ECONOMY PRACTICES IN SEMARANG - Pramono, Sugiarto (Laporan Penelitian dan Pengabdian Masyarakat, 2023)
This research delves into the implementation of a circular economy in Semarang City, responding to thechallenges of waste management and its environmental impacts. Employing a methodology combiningliterature review and stakeholder interviews, the study analyzes the principles of a circular economy andthe pivotal roles of key actors in its practical application. The theoretical foundation rests upon the conceptsof a circular economy, waste management, and sustainability. The findings indicate progress inimplementation, particularly through the establishment of waste banks and waste management programsinvolving households. The significant roles of the City Government, Mulung Parahita, and the IndonesianNational Army (TNI) are acknowledged, though challenges such as coordination and public awarenessneed to be addressed. The contribution lies in a profound understanding of the circular economy inSemarang City and the identification of key roles and actors. The policy recommendations generated canguide the efforts of the City Government and relevant stakeholders to reinforce circular economy practices,promoting more sustainable resource management at the local level. Keywords: circular economy, waste management, Semarang City, waste bank, sustainability, communityparticipation